BRAIN AND BEHAVIOR – HYPOTHALAMUS AND LIMBIC SYSTEM: THE NEUROBIOLOGY OF EMOTIONS - S, Anjali Daisy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
It is intuitive to understand how sensory information gets to the brain and how motor information can travel to the muscles together where these twosystems allow us to detect and respond to the world around us but how do we engage with that world, how do we determine what is important, andhow do we fall in the analysis. These higher cortical functions involve the complex interplay between neurotransmitters and hormones throughout theentire nervous system. There are two major anatomical behaviors; the limbic system and hypothalamus. These structures that support much highercortical functions hypothalamus is a very small structure but it is absolutely critical for life and it allows us to respond to both the internal and externalenvironment and to maintain homeostasis. The limbic system is important for learning and memory, and all emotional aspects of behavior importantlylimbic and hypothalamic structures are interconnected with each other. Let's begin with an anatomical overview of the hypothalamus in the middlesection. You can delineate the hypothalamus from the thalamus through the hypothalamic sulcus anteriorly, the hypothalamus extends to the anteriorcommissure, and the optic chiasm inferiorly and it includes the mammillary bodies and extends to the infundibula stock where it communicateswith the pituitary glands. It is a coronal section through the brain. It is the third ventricle, you can identify the thalamus on either side of the thirdventricle and underneath; the thalamus is the hypothalamus and it extends laterally to these descending fiber bundles which are part of the internalcapsule. The hypothalamus is structurally part of the diencephalon but it functions as part of the limbic system through reciprocal connections. Ithelps to maintain homeostasis in the entire body through influences on the endocrine system and importantly through its primary influence onboth the sympathetic and parasympathetic systems; the limbic system is extremely old from an evolutionary perspective in its connections and it isinterposed between the hypothalamus and the neocortex and providing a bridge between endocrine visceral emotional and voluntary responses tothe environment.